Aerogel-based porous composite material for sewage treatment as well as preparation method and application of aerogel-based porous composite material

Through the synergistic effect of the nanocellulose framework and ZIF-67 crystal and directional freezing, aerogel-based porous composite materials are prepared, which solves the problems of limited adsorption capacity and insufficient catalytic activity of existing wastewater treatment materials when treating complex water bodies, and achieves efficient removal of dyes, hydrocarbon pollutants and heavy metal ions, improving mass transfer efficiency and selective adsorption capacity.

CN120268457AActive Publication Date: 2025-07-08SINO-SINGAPORE RUIMEI (TIANJIN) ENVIRONMENTAL PROTECTION TECH CO LTD +2

Patent Information

Application Number
CN202510743369.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-07-08
Estimated Expiration
2045-06-05

AI Technical Summary

Technical Problem

When treating industrial wastewater containing high concentrations of organic matter, heavy metal ions and complex pollutants, existing wastewater treatment materials have problems such as limited adsorption capacity, easy saturation, difficulty in regeneration, insufficient selectivity to hydrophobic pollutants, easy deactivation of catalytic active sites, narrow pH application range and risk of metal ions dissolution. Especially when treating oil-containing wastewater, it has strong hydrophilicity and poor oleophobicity, resulting in intensification of oil-water emulsification and poor separation effect.

Method used

The synergistic effect of the nanocellulose framework and ZIF-67 crystal is adopted to construct a multi-stage pore structure in combination with directional cryogenic. Through efficient coordination of physical adsorption and chemical catalysis, aerogel-based porous composite materials are prepared to achieve efficient removal of dyes, hydrocarbon pollutants and heavy metal ions.

Benefits of technology

Within a wide pH range (pH=3~11), it shows excellent removal effect on pollutants in printing and dyeing wastewater and petrochemical wastewater, improving mass transfer efficiency and selective adsorption capacity, and maintaining the structural integrity and mechanical strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120268457A_ABST
    Figure CN120268457A_ABST
Patent Text Reader

Abstract

The invention provides an aerogel-based porous composite material for sewage treatment and a preparation method and application thereof.The preparation method comprises the steps that a nanocellulose solution and a cobalt source solution are mixed to obtain a precursor solution, and under the stirring and heating conditions, an organic ligand solution is dropwise added into the precursor solution to obtain a reaction solution; uniformly mixing the reaction solution with polyvinyl alcohol, injecting the mixture into a mold, and performing directional freezing to obtain an aerogel matrix; and carrying out hydrophobic modification on the aerogel matrix. Through the synergistic effect of the nanocellulose skeleton and the ZIF-67 crystal, and in combination with a hierarchical porous structure constructed by directional freezing, efficient synergism of physical adsorption and chemical catalysis is realized, so that the material shows an excellent removal effect on dyes, hydrocarbon pollutants and heavy metal ions in complex water bodies such as printing and dyeing wastewater and petrochemical wastewater in a wide pH range (pH = 3-11).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage treatment, and relates to an aerogel-based porous composite material for sewage treatment, a preparation method and uses thereof. Background Art

[0002] Sewage treatment is an important part of environmental protection. With the acceleration of industrialization and urbanization, the discharge of industrial wastewater containing high concentrations of organic matter, heavy metal ions and complex pollutants (such as printing and dyeing wastewater, petrochemical wastewater) is increasing day by day, and traditional treatment technologies are facing severe challenges. Existing adsorption materials (such as activated carbon, resins, etc.) generally have problems such as limited adsorption capacity, easy saturation, difficulty in regeneration, etc., and have insufficient selectivity for hydrophobic pollutants; although the biodegradation method is sustainable, it is limited by the sensitivity of microbial activity to environmental conditions, with a long treatment cycle and unstable efficiency; catalytic materials based on metal oxides or polymers can accelerate the decomposition of pollutants, but have defects such as easy inactivation of catalytic active sites, narrow pH application range, and high risk of metal ion leaching. In addition, most existing materials have a single pore structure and low mass transfer efficiency, making it difficult to achieve the synergistic effect of rapid capture and efficient degradation of pollutants. Especially when treating oily wastewater, traditional materials have strong hydrophilicity and poor oleophobicity, which easily leads to aggravated oil-water emulsification and poor separation effect.

[0003] In view of the above problems, there is an urgent need to develop a new type of sewage treatment material with high specific surface area, hierarchical pore structure, wide pH adaptability, strong hydrophobic and oleophilic properties, and catalytic-adsorption-biodegradation synergistic function to achieve the efficient purification and resource utilization of complex water quality. Summary of the Invention

[0004] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide an aerogel-based porous composite material for sewage treatment, a preparation method and uses thereof. Through the synergistic effect of a nanocellulose skeleton and ZIF-67 crystals, combined with a hierarchical pore structure constructed by directional freezing, the efficient synergy of physical adsorption and chemical catalysis is realized, so that the material shows excellent removal effects on dyes, hydrocarbon pollutants and heavy metal ions in complex water bodies such as printing and dyeing wastewater and petrochemical wastewater within a wide pH range (pH = 3 - 11).

[0005] To achieve this purpose, the present invention adopts the following technical solutions:

[0006] In the first aspect, the present invention provides a preparation method of an aerogel-based porous composite material for sewage treatment, and the preparation method includes:

[0007] Mix the nanocellulose solution with the cobalt source solution to obtain a precursor solution. Under stirring and heating conditions, drop the organic ligand solution into the precursor solution to obtain a reaction solution; mix the reaction solution with polyvinyl alcohol evenly and then inject it into a mold for directional freezing to obtain an aerogel matrix; perform hydrophobic modification on the aerogel matrix to obtain the aerogel-based porous composite material.

[0008] Through the synergistic effect of the nanocellulose framework and ZIF-67 crystals, combined with the hierarchical pore structure constructed by directional freezing, the present invention realizes the efficient synergy of physical adsorption and chemical catalysis, enabling the material to exhibit excellent removal effects on dyes, hydrocarbon pollutants, and heavy metal ions in complex water bodies such as printing and dyeing wastewater and petrochemical wastewater within a wide pH range (pH = 3 - 11).

[0009] The present invention uses nanocellulose as a biomass framework material and utilizes the coordination of its abundant surface hydroxyl functional groups with cobalt ions. When the cobalt nitrate solution is mixed with nanocellulose, cobalt ions are preferentially adsorbed around the oxygen-containing groups of the cellulose molecular chain, forming a uniform metal ion distribution network. Subsequently, the introduced 2-methylimidazole organic ligand undergoes a self-assembly reaction with cobalt ions to generate the metal-organic framework material ZIF-67 in the interstices of the nanocellulose network. The excess organic ligand not only ensures the complete progress of the reaction but also inhibits the overgrowth of crystals through steric hindrance effects, ultimately forming regular dodecahedral crystals.

[0010] ZIF-67 crystals are tightly bound to the nanocellulose network through hydrogen bonding, retaining both the three-dimensional pore structure of the aerogel matrix and endowing it with catalytic active sites, capable of rapidly capturing heavy metal ions (such as Pb 2+ 、Cd 2+ ), organic dye molecules, and oil pollutants in wastewater; at the same time, its Lewis acidic sites (Co 2+ nodes) can also bind to specific pollutants (such as sulfur- or nitrogen-containing compounds) through coordination, enhancing selective adsorption.

[0011] The unique coordinatively unsaturated metal sites (Co 2+ ) of ZIF-67 crystals have redox activity. Under acidic conditions (pH < 7), Co 2+ is easily oxidized to Co 3+ , forming oxygen vacancy defects, significantly enhancing the catalytic decomposition ability of organic matter; while in an alkaline environment (pH > 7), the surface of the material is negatively charged, and cationic dye molecules can be enriched through electrostatic attraction. At the same time, the Lewis acidic sites of ZIF-67 promote the decolorization reaction of dye molecules. This pH self-adaptive characteristic enables the aerogel-based porous composite material to maintain high catalytic performance under complex water quality conditions (such as a wide pH fluctuation range in printing and dyeing wastewater).

[0012] The present invention forms a hierarchical pore structure with vertically arranged micron-sized macropores and nanometer-sized mesopores intertwined through a directional freezing process. The macropores (50 - 200 μm) provide rapid penetration channels for pollutants, significantly enhancing the mass transfer efficiency of pollutants; while the mesopore structure (2 - 5 μm) formed by the in-situ growth of ZIF-67 crystals in the gaps of nanocellulose forms high-density active sites. This hierarchical pore structure maximizes the specific surface area of the material, enabling it to rapidly capture hydrophobic organic compounds through physical interactions such as van der Waals forces and π-π stacking, and also intercept charged pollutants through electrostatic adsorption on the inner wall of the pores.

[0013] The present invention realizes the hydrophobic modification of the aerogel matrix through the hydrolysis and condensation reaction of silane coupling agents. In an ethanol-water mixed system, the methoxy groups of the silane coupling agent first hydrolyze to generate reactive silanol groups, and these highly reactive groups undergo dehydration condensation with the hydroxyl groups on the surface of the aerogel matrix to form stable Si-O-C covalent bonds. The long-chain alkyl groups grafted onto the surface of the aerogel matrix form a dense monolayer, raising the water contact angle of the aerogel matrix surface to over 145°. This chemical modification not only endows the aerogel matrix with hydrophobic properties, but also produces a selective adsorption effect due to the change in its microscopic surface energy, that is, non-polar oily pollutants are more easily adsorbed due to surface tension differences, while water molecules are excluded, resulting in hydrophobic and lipophilic properties. After hydrophobic modification, the aerogel matrix maintains its porous structure, and due to the coating and reinforcement effect of the silane layer on the aerogel matrix, its mechanical strength is also significantly improved.

[0014] As a preferred technical solution of the present invention, the mass fraction of the nanocellulose solution is 1 - 2 wt%, for example, it can be 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2.0 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0015] In some alternative examples, the cobalt source solution is composed of cobalt nitrate and deionized water.

[0016] In some alternative examples, the concentration of cobalt nitrate in the cobalt source solution is 0.15 - 0.25 mol / L, for example, it can be 0.15 mol / L, 0.16 mol / L, 0.17 mol / L, 0.18 mol / L, 0.19 mol / L, 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L or 0.25 mol / L, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0017] In some alternative examples, the volume ratio of the nanocellulose solution to the cobalt source solution is (2 - 3):1. For example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0018] The present invention specifically defines the volume ratio of the nanocellulose solution to the cobalt source solution as (2 - 3):1. As the core component of the aerogel skeleton, the dosage of nanocellulose directly affects the cross - linking density of the fiber network and the coordination efficiency of cobalt ions. When the volume ratio of the nanocellulose solution to the cobalt source solution is within the range defined by the present invention, the hydroxyl groups on the nanocellulose chain can form an appropriate coordination interaction with cobalt ions, ensuring that sufficient metal ions are anchored on the surface of the nanocellulose network while avoiding the destruction of the hydrogen - bond cross - linking structure of nanocellulose by excessive cobalt salts. This enables the subsequent addition of 2 - methylimidazole organic ligands to be evenly distributed in the gaps of the cellulose network and combine with cobalt ions to generate ZIF - 67 crystals with uniform size, constructing a stable hierarchical pore structure for the aerogel matrix.

[0019] When the addition amount of the nanocellulose solution is too low, the concentration of cobalt ions is too high, causing the coordination reaction to concentrate in local areas. The ZIF - 67 crystals over - grow to form large - size aggregates, which not only block the pores of the aerogel matrix, reducing its porosity, but also weaken the mechanical strength of the nanocellulose network. At the same time, the unreacted free cobalt ions will crystallize out during the directional freezing process, destroying the regularity of the pore structure of the aerogel matrix.

[0020] When the addition amount of the nanocellulose solution is too high, the excessive nanocellulose chains hinder the uniform distribution of cobalt ions due to steric hindrance effects, resulting in insufficient nucleation sites for ZIF - 67 crystals. Eventually, the formed ZIF - 67 crystals have poor dispersion and a reduced density of catalytic active sites. At the same time, the dense network formed by excessive cross - linking of nanocellulose will compress the pore space, significantly reducing the specific surface area of the aerogel matrix.

[0021] As a preferred technical solution of the present invention, the organic ligand solution is composed of 2 - methylimidazole and methanol.

[0022] In some optional examples, the concentration of 2-methylimidazole in the organic ligand solution is 0.9 - 1 mol / L. For example, it can be 0.9 mol / L, 0.91 mol / L, 0.92 mol / L, 0.93 mol / L, 0.94 mol / L, 0.95 mol / L, 0.96 mol / L, 0.97 mol / L, 0.98 mol / L, 0.99 mol / L or 1 mol / L. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0023] In some optional examples, the dropping rate of the organic ligand solution is 1.5 - 2.5 mL / min. For example, it can be 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min, 2.0 mL / min, 2.1 mL / min, 2.2 mL / min, 2.3 mL / min, 2.4 mL / min or 2.5 mL / min. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0024] In some optional examples, the molar ratio of 2-methylimidazole in the organic ligand solution to cobalt ions in the cobalt source solution is (5 - 6):1. For example, it can be 5.0:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1 or 6.0:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0025] In the aerogel-based porous composite material, ZIF-67 serves as the core catalytic active component. The molar ratio of the organic ligand 2-methylimidazole to cobalt ions directly affects its photocatalytic performance. The present invention specifically defines that the molar ratio of 2-methylimidazole in the organic ligand solution to cobalt ions in the cobalt source solution is (5 - 6):1. Within this molar ratio range, the coordination saturation of cobalt ions is moderate, which can not only form a complete dodecahedral ZIF-67 crystal structure but also avoid the steric hindrance caused by excessive organic ligands. At the same time, the appropriate molar ratio enables the obtained ZIF-67 crystals to efficiently separate photogenerated carriers under light illumination, promoting the generation of hydroxyl radicals and superoxide radicals, thereby significantly enhancing the photocatalytic degradation efficiency of organic pollutants.

[0026] When the addition amount of 2-methylimidazole is lower than the lower limit of the range defined in the present invention, the concentration of cobalt ions is relatively high, resulting in intensified competitive adsorption of cobalt ions in the coordination reaction. Since cobalt ions cannot be completely coordinated, some cobalt ions will exist in the solution in a free state or form defect sites on the crystal surface, leading to uneven distribution of crystal particle sizes, hindering the effective contact between pollutant molecules and catalytic sites, and further reducing the mass transfer efficiency of the photocatalytic reaction.

[0027] When the addition amount of 2-methylimidazole is higher than the upper limit of the range defined in the present invention, the excessive 2-methylimidazole causes the organic ligand to dominate in the crystal growth process. The excessive organic ligand will form a dense organic layer on the surface of ZIF-67, hindering the migration and separation of photo-generated electron-hole pairs and inhibiting the activity of the catalytic reaction. In addition, the high concentration of organic ligands will also increase the solution viscosity, slow down the diffusion rate of reactants, affect the uniformity of ZIF-67 crystal growth, and ultimately lead to poor dispersion of ZIF-67 particles loaded in the aerogel matrix and a decline in catalytic performance.

[0028] In some alternative examples, the heating temperature when the organic ligand solution is dropped into the precursor solution is 60-70 °C, for example, it can be 60 °C, 61 °C, 62 °C, 63 °C, 64 °C, 65 °C, 66 °C, 67 °C, 68 °C, 69 °C or 70 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0029] In some alternative examples, after all the organic ligand solution is dropped, the resulting mixture is continuously mixed and stirred for 4-5 h to obtain the reaction solution. For example, it can be 4.0 h, 4.1 h, 4.2 h, 4.3 h, 4.4 h, 4.5 h, 4.6 h, 4.7 h, 4.8 h, 4.9 h or 5.0 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0030] As a preferred technical solution of the present invention, the addition amount of polyvinyl alcohol is 7-9 wt% of the mass of the reaction solution. For example, it can be 7.0 wt%, 7.2 wt%, 7.4 wt%, 7.6 wt%, 7.8 wt%, 8.0 wt%, 8.2 wt%, 8.4 wt%, 8.6 wt%, 8.8 wt% or 9.0 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0031] The present invention specifically limits the addition amount of polyvinyl alcohol (PVA) to 7-9 wt% of the mass of the reaction solution. PVA plays a dual role in the reaction system: on the one hand, as an adhesive, hydrogen bond networks are formed between the hydroxyl groups on its molecular chain and the hydroxyl groups on the surface of nanocellulose, significantly enhancing the interfacial binding force between nanocellulose and ZIF-67 crystals, and preventing the ZIF-67 crystals from falling off due to mechanical disturbance during subsequent freeze-drying or sewage treatment processes; on the other hand, as an ice crystal growth regulator, the flexible structure of the PVA molecular chain can interfere with the free arrangement of water molecules, guiding the ice crystals to grow orderly along a specific direction, thereby regulating the pore structure of the aerogel matrix. When the addition amount of PVA is within the range defined by the present invention, its hydrogen bond effect can not only effectively fix the ZIF-67 crystals, but also not overly hinder the self-assembly process of the nanocellulose network, promoting the formation of vertically penetrating micron-sized pores in the aerogel matrix, making the material have both high pollutant mass transfer efficiency and sufficient exposed catalytic active sites.

[0032] When the addition amount of PVA is less than 7 wt%, its bonding ability is significantly weakened, and the interfacial binding force between nanocellulose and ZIF-67 crystals is insufficient, resulting in the easy aggregation of ZIF-67 crystals or peeling from the surface of the aerogel matrix during the freeze-drying process. This will not only reduce the mechanical stability of the material, but also decrease the number of effective active sites actually participating in the catalytic reaction. In addition, when the PVA content is insufficient, its regulation effect on ice crystal growth will also be weakened, resulting in disordered growth of ice crystals, and the formed pore structure shows a chaotic distribution state, with poor pore connectivity, hindering the diffusion and transmission of pollutant molecules inside the material, and thus affecting the adsorption and catalytic efficiency of the aerogel matrix composite material.

[0033] When the addition amount of PVA exceeds 9 wt%, excessive PVA molecules will overly occupy the space sites in the nanocellulose network, forming a dense hydrogen bond network. The excessive cross-linking effect limits the flexibility of the nanocellulose itself, hindering its formation of an ordered pore structure during the directional freezing process. In addition, the increase in the amount of PVA used will also change ice crystal nucleation and growth, resulting in the ice crystal size tending to be small and unevenly distributed, leading to a significant reduction in the specific surface area and porosity of the material, making it difficult for pollutant molecules to effectively enter the material and contact the ZIF-67 active sites.

[0034] In some optional examples, the mixing and stirring time of the reaction solution and the polyvinyl alcohol is 2-4 h. For example, it can be 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4.0 h, but it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0035] As a preferred technical solution of the present invention, the directional freezing process includes:

[0036] Cooling to a first freezing temperature at a first cooling rate and holding the temperature, and then continuing to cool to a second freezing temperature at a second cooling rate and holding the temperature.

[0037] In the present invention, in the first cooling stage, it is rapidly cooled to -15 to -20°C at a rate of -1 to -2°C / min, so as to promote the formation of a large number of tiny ice crystal nuclei in the solution. During the heat preservation process, the ice crystals initially extend and grow along the temperature gradient direction to form an initial pore framework with a diameter of about 50 to 150 μm. In the second cooling stage, it is slowly cooled to -30 to -40°C at a rate of -0.5 to -1°C / min. At this time, the solution viscosity increases significantly, and a secondary microporous structure is induced to form on the wall surface of the formed initial pores. During the heat preservation process, the solvent molecules in the remaining unfrozen liquid phase are fully crystallized to avoid stress concentration caused by rapid deep cooling, and finally a multi-stage pore structure in which vertically arranged through pores and wall micropores are intertwined is formed. This multi-stage pore structure directly affects the sewage treatment effect of the material. The through large-diameter channels greatly improve the pollutant adsorption rate, and the secondary microporous structure formed on the wall surface of the large-diameter channels provides a high-density anchoring site for the loading of ZIF-67 crystals.

[0038] As a preferred technical solution of the present invention, the first cooling rate is -1 to -2°C / min. For example, it can be -1°C / min, -1.1°C / min, -1.2°C / min, -1.3°C / min, -1.4°C / min, -1.5°C / min, -1.6°C / min, -1.7°C / min, -1.8°C / min, -1.9°C / min or -2°C / min, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0039] In some alternative examples, the first freezing temperature is -15 to -20°C. For example, it can be -15°C, -15.5°C, -16°C, -16.5°C, -17°C, -17.5°C, -18°C, -18.5°C, -19°C, -19.5°C or -20°C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0040] In some alternative examples, the heat preservation time at the first freezing temperature is 0.5 to 1.5 h. For example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0041] In some alternative examples, the second cooling rate is -0.5 to -1 °C / min. For example, it can be -0.5 °C / min, -0.55 °C / min, -0.6 °C / min, -0.65 °C / min, -0.7 °C / min, -0.75 °C / min, -0.8 °C / min, -0.85 °C / min, -0.9 °C / min, -0.95 °C / min or -1 °C / min. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0042] In some alternative examples, the second freezing temperature is -30 to -40 °C. For example, it can be -30 °C, -31 °C, -32 °C, -33 °C, -34 °C, -35 °C, -36 °C, -37 °C, -38 °C, -39 °C or -40 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0043] The present invention specifically defines the second freezing temperature as -30 to -40 °C. The second freezing stage is a key link in determining the microscopic morphology of the aerogel matrix. On the basis of the initial ice crystal nuclei formed by the rapid cooling in the previous stage, a more gentle cooling rate is required in the second stage to guide the ice crystals to extend orderly along the temperature gradient direction. When the second freezing temperature is set at -30 °C to -40 °C, the solution viscosity is moderate, and the growth rate of ice crystals is significantly reduced due to the influence of viscosity retardation. This helps the nano-cellulose network and ZIF-67 crystals to be fully arranged in the ice crystal gaps. At this time, the formed ice crystal size is uniform, and the ice crystal wall can induce the formation of mesoporous structures. This hierarchical pore structure not only ensures the through-channel for the rapid penetration of pollutant molecules but also provides sufficient space for catalytic active sites.

[0044] When the second freezing temperature is higher than -30 °C, the solution viscosity drops sharply, and the ice crystal growth rate increases, resulting in an increase in ice crystal size. The rapidly growing ice crystals will squeeze the nano-cellulose network, causing the pore structure to coarsen, the pore walls to become thinner and prone to collapse, and finally forming a loose aerogel structure, resulting in a decrease in the pollutant adsorption capacity of the aerogel matrix.

[0045] When the second freezing temperature is lower than -40 °C, the viscosity of the solution system is too high, resulting in a sharp increase in the ice crystal nucleation density, forming a large number of randomly oriented small ice crystals, and finally leading to the densification of the aerogel matrix, a significant decrease in pore connectivity, and a significant increase in the pollutant mass transfer resistance.

[0046] In some alternative examples, the heat preservation time at the second freezing temperature is 3 to 4 hours. For example, it can be 3.0 h, 3.1 h, 3.2 h, 3.3 h, 3.4 h, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h or 4.0 h, but it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0047] As a preferred technical solution of the present invention, the hydrophobic modification treatment includes:

[0048] Immerse the aerogel matrix in a silane coupling agent solution, oscillate and heat it. Subsequently, take out the aerogel matrix, wash it with ethanol and then perform vacuum drying to obtain the aerogel-based porous composite material.

[0049] During the modification process, the silanol groups generated by the hydrolysis of the silane coupling agent undergo a condensation reaction with the hydroxyl groups on the surface of the aerogel matrix to form a dense Si-O-Si covalent bond network. The directional arrangement of the long-chain alkyl groups makes the surface contact angle of the aerogel matrix reach more than 145°. On the one hand, this chemical modification endows the aerogel matrix with superhydrophobic properties, which can effectively block the penetration of water molecules and prevent the hydrolysis reaction of ZIF-67 crystals in the water environment, resulting in the dissolution of cobalt ions, so that the aerogel-based porous composite material maintains structural integrity in a wide range of pH = 3 to 11. On the other hand, the silane layer grafted on the surface of the aerogel matrix can also reinforce the node connection of cellulose fibers through intermolecular forces, significantly improving the anti-swelling ability of the finally prepared aerogel-based composite material in the aqueous phase environment.

[0050] As a preferred technical solution of the present invention, the silane coupling agent solution is composed of a silane coupling agent and an ethanol aqueous solution.

[0051] In some alternative examples, the mass fraction of the silane coupling agent in the silane coupling agent solution is 1.8 to 2.2 wt%. For example, it can be 1.8 wt%, 1.85 wt%, 1.9 wt%, 1.95 wt%, 2.0 wt%, 2.05 wt%, 2.1 wt%, 2.15 wt% or 2.2 wt%, but it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0052] The role of the silane coupling agent is to introduce hydrophobic groups onto the surface of the aerogel matrix through chemical bonding to construct a superhydrophobic / oleophilic surface. The present invention specifically limits the mass fraction of the silane coupling agent in the silane coupling agent solution to 1.8 to 2.2 wt%. Within this range, it can not only ensure the uniform coverage of silane molecules on the surface of the aerogel matrix to form a dense hydrophobic layer, but also avoid intermolecular aggregation or excessive crosslinking caused by too high a concentration, thereby improving the hydrophobic performance of the material while maintaining the openness of the pore structure.

[0053] When the mass fraction of the silane coupling agent is less than 1.8 wt%, its coverage rate on the surface of the aerogel matrix is insufficient. At this time, the hydrophobic groups cannot form a continuous hydrophobic barrier, resulting in the retention of some hydrophilic regions on the surface of the finally obtained aerogel matrix, which will weaken the capture ability of the aerogel matrix for oil droplets and hydrophobic pollutants.

[0054] When the mass fraction of the silane coupling agent exceeds 2.2 wt%, excessive silane molecules will form a dense hydrophobic layer on the surface of the aerogel matrix, which will hinder the diffusion of pollutant molecules into the internal pores of the aerogel matrix and reduce the mass transfer efficiency. In addition, a high concentration of silane coupling agent will also cause agglomeration on the surface of the aerogel matrix due to too violent hydrolysis reaction, forming rough hydrophobic patches, thus destroying the original hierarchical porous structure of the aerogel matrix.

[0055] In some alternative examples, the heating temperature when the aerogel matrix is immersed in the silane coupling agent solution is 35 - 45 °C, for example, it can be 35 °C, 36 °C, 37 °C, 38 °C, 39 °C, 40 °C, 41 °C, 42 °C, 43 °C, 44 °C or 45 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0056] In some alternative examples, the immersion time of the aerogel matrix in the silane coupling agent solution is 12 - 24 h, for example, it can be 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0057] In some alternative examples, the temperature of the vacuum drying is 45 - 55 °C, for example, it can be 45 °C, 46 °C, 47 °C, 48 °C, 49 °C, 50 °C, 51 °C, 52 °C, 53 °C, 54 °C or 55 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0058] In some alternative examples, the time of the vacuum drying is 10 - 12 h, for example, it can be 10 h, 10.2 h, 10.4 h, 10.6 h, 10.8 h, 11 h, 11.2 h, 11.4 h, 11.6 h, 11.8 h or 12 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0059] In a second aspect, the present invention provides an aerogel-based porous composite material for sewage treatment prepared by using the preparation method described in the first aspect.

[0060] In a third aspect, the present invention provides a use of the aerogel-based porous composite material for sewage treatment described in the second aspect, where the aerogel-based porous composite material is used for sewage treatment.

[0061] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0062] Through the synergistic effect of the nanocellulose framework and ZIF-67 crystals, combined with the hierarchically porous structure constructed by directional freezing, the present invention achieves efficient synergy of physical adsorption and chemical catalysis, enabling the material to exhibit excellent removal effects on dyes, hydrocarbon pollutants, and heavy metal ions in complex water bodies such as printing and dyeing wastewater and petrochemical wastewater within a wide pH range (pH = 3 - 11). BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 is a process flow chart for the preparation of the aerogel-based porous composite material provided in Examples 1 - 15 of the present invention;

[0064] Figure 2 is an infrared spectrum diagram of nanocellulose, ZIF-67, and the aerogel-based porous composite material prepared in Example 1 of the present invention;

[0065] Figure 3 is an XRD spectrum diagram of nanocellulose, ZIF-67, and the aerogel-based porous composite material prepared in Example 1 of the present invention;

[0066] Figure 4 is a test curve graph of the water contact angle and oil contact angle of the aerogel-based porous composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0067] The technical solutions of the present invention will be described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments described herein are specific specific embodiments of the present invention for explaining the concept of the present invention; these descriptions are all explanatory and exemplary, and should not be construed as limiting the embodiments of the present invention and the protection scope of the present invention. Except for the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of the present application, and these technical solutions include technical solutions that make any obvious substitutions and modifications to the embodiments described herein.

[0068] Example 1

[0069] This example provides a method for preparing an aerogel-based porous composite material for sewage treatment, as Figure 1 shown, the preparation method specifically includes the following steps:

[0070] (1) Disperse cobalt nitrate in deionized water. After mixing evenly, a cobalt source solution with a concentration of 0.15 mol / L is obtained. Mix a nanocellulose solution with a mass fraction of 1 wt% and the cobalt source solution according to a volume ratio of 3:1 to obtain a precursor solution. Disperse 2-methylimidazole in methanol. After mixing evenly, an organic ligand solution with a concentration of 0.9 mol / L is obtained. Under stirring and heating at 60 °C, the organic ligand solution is dropped into the precursor solution at a rate of 1.5 mL / min. The molar ratio of 2-methylimidazole to cobalt ions is 5:1. After all the organic ligand solution is dropped, continue to stir the obtained mixture at 60 °C for 5 h to obtain a reaction solution.

[0071] (2) Mix the reaction solution and polyvinyl alcohol and stir for 2 h. The addition amount of polyvinyl alcohol is 7 wt% of the mass of the reaction solution. Inject the mixed solution into a mold for directional freezing. First, cool down to -15 °C at a cooling rate of -1 °C / min and keep it warm for 1.5 h. Then continue to cool down to -30 °C at a cooling rate of -0.5 °C / min and keep it warm for 4 h to obtain an aerogel matrix.

[0072] (3) Add silane coupling agent KH550 to an ethanol aqueous solution (the volume ratio of absolute ethanol to deionized water in the ethanol aqueous solution is 9:1). After mixing evenly, a silane coupling agent solution with a mass fraction of 1.8 wt% is obtained. Immerse the aerogel matrix in the silane coupling agent solution and oscillate at 35 °C for 24 h. Then take out the aerogel matrix, wash it with ethanol, and place it in a vacuum dryer at 45 °C for 12 h to obtain the aerogel-based porous composite material.

[0073] Figure 2 are the infrared spectra of nanocellulose, ZIF-67, and the aerogel-based porous composite material prepared in this example. It can be seen from the figure that in the infrared spectrum of nanocellulose, the characteristic peaks at 3460 cm -1 and 1735 cm -1 are respectively attributed to the C-H stretching of cellulose hydroxyl and the C=O stretching vibration of carboxyl. In the infrared spectrum of the aerogel matrix obtained by in-situ growth of ZIF-67 nanoparticles, the absorption band appearing at 422 cm -1 is attributed to the Co-N stretching vibration of ZIF-67. The vibration peaks at 1382 cm -1 , 1417 cm -1 and 1453 cm -1 are attributed to the C-N bond stretching vibration of 2-methylimidazole. The characteristic peaks at 689 cm -1 , 753 cm -1 and 1306 cm -1 are attributed to the bending vibration of 2-methylimidazole. The above results indicate that ZIF-67 nanoparticles are successfully loaded on the aerogel matrix.

[0074] Figure 3 XRD patterns of nanocellulose, ZIF-67 and the aerogel-based porous composite prepared in this example. It can be seen from the figure that the main diffraction peaks at 2θ of 7.4°, 10.4°, 12.7°, 18.1° and 26.7° correspond to the (011), (002), (112), (222) and (134) crystal planes of ZIF-67, respectively. In addition, in the XRD pattern of the aerogel matrix, the weak characteristic peak at 22.6° belongs to the (002) crystal plane of nanocellulose. The above results indicate that ZIF-67 is successfully loaded on the aerogel matrix.

[0075] Figure 4 Test curve graphs of the water contact angle and oil contact angle of the aerogel-based porous composite prepared in this example. It can be seen from the figure that as the test time prolongs, the surface water contact angle of the aerogel-based porous composite slightly decreases, but its average value is 145°, still belonging to a superhydrophobic surface; similarly, as the test time prolongs, the surface oil contact angle of the aerogel-based porous composite also slightly decreases, but its average value is 10°, belonging to a superoleophilic surface, which indicates that the aerogel-based porous composite obtained after modification with silane coupling agent has hydrophobic and oleophilic properties.

[0076] Example 2

[0077] This example provides a preparation method of an aerogel-based porous composite for sewage treatment, as Figure 1 shown. The specific preparation method includes the following steps:

[0078] (1) Disperse cobalt nitrate in deionized water, and after mixing evenly, a cobalt source solution with a concentration of 0.18 mol / L is obtained. Mix the nanocellulose solution with a mass fraction of 1.2 wt% and the cobalt source solution evenly according to a volume ratio of 2.8:1 to obtain a precursor solution; disperse 2-methylimidazole in methanol, and after mixing evenly, an organic ligand solution with a concentration of 0.92 mol / L is obtained. Under the conditions of stirring and heating at 62 °C, the organic ligand solution is dropped into the precursor solution at a speed of 1.8 mL / min. The molar ratio of 2-methylimidazole to cobalt ions is 5.2:1. After all the organic ligand solution is dropped, continue to stir the obtained mixture at 62 °C for 4.8 h to obtain a reaction solution;

[0079] (2) Mix the reaction solution with polyvinyl alcohol and stir for 2.5 h. The addition amount of polyvinyl alcohol is 7.5 wt% of the mass of the reaction solution. Inject the mixed solution into a mold for directional freezing. First, cool it at a cooling rate of -1.2 °C / min to -16 °C and keep it warm for 1.2 h. Then, continue to cool it at a cooling rate of -0.6 °C / min to -32 °C and keep it warm for 3.8 h to obtain an aerogel matrix;

[0080] (3) Add silane coupling agent KH550 to an ethanol aqueous solution (the volume ratio of absolute ethanol to deionized water in the ethanol aqueous solution is 9:1). After mixing evenly, obtain a silane coupling agent solution with a mass fraction of 1.9 wt%. Immerse the aerogel matrix in the silane coupling agent solution and oscillate at 38 °C for 21 h. Then take out the aerogel matrix, wash it with ethanol, and place it in a vacuum dryer at 48 °C for 11.5 h to obtain the aerogel-based porous composite material.

[0081] Example 3

[0082] This example provides a preparation method of an aerogel-based porous composite material for sewage treatment. As Figure 1 shown, the preparation method specifically includes the following steps:

[0083] (1) Disperse cobalt nitrate in deionized water. After mixing evenly, obtain a cobalt source solution with a concentration of 0.2 mol / L. Mix the nano-cellulose solution with a mass fraction of 1.5 wt% and the cobalt source solution according to a volume ratio of 2.5:1 to obtain a precursor solution. Disperse 2-methylimidazole in methanol. After mixing evenly, obtain an organic ligand solution with a concentration of 0.95 mol / L. Under the conditions of stirring and heating at 65 °C, drip the organic ligand solution into the precursor solution at a speed of 2 mL / min. The molar ratio of 2-methylimidazole to cobalt ions is 5.5:1. After all the organic ligand solution is dripped, continue to stir the obtained mixture at 65 °C for 4.5 h to obtain a reaction solution;

[0084] (2) Mix the reaction solution with polyvinyl alcohol and stir for 3 h. The addition amount of polyvinyl alcohol is 8 wt% of the mass of the reaction solution. Inject the mixed solution into a mold for directional freezing. First, cool it at a cooling rate of -1.5 °C / min to -17 °C and keep it warm for 1 h. Then, continue to cool it at a cooling rate of -0.7 °C / min to -35 °C and keep it warm for 3.5 h to obtain an aerogel matrix;

[0085] (3) Add silane coupling agent KH550 into an ethanol aqueous solution (the volume ratio of absolute ethanol to deionized water in the ethanol aqueous solution is 9:1). After mixing evenly, a silane coupling agent solution with a mass fraction of 2 wt% is obtained; Immerse the aerogel matrix in the silane coupling agent solution, oscillate at 40 °C for 18 h, then take out the aerogel matrix, wash it with ethanol, and place it in a vacuum dryer at 50 °C for 11 h to obtain the aerogel-based porous composite material.

[0086] Example 4

[0087] This example provides a preparation method of an aerogel-based porous composite material for sewage treatment, as Figure 1 shown, the preparation method specifically includes the following steps:

[0088] (1) Disperse cobalt nitrate in deionized water. After mixing evenly, a cobalt source solution with a concentration of 0.22 mol / L is obtained. Mix the nanocellulose solution with a mass fraction of 1.8 wt% and the cobalt source solution according to a volume ratio of 2.2:1 to obtain a precursor solution; Disperse 2-methylimidazole in methanol. After mixing evenly, an organic ligand solution with a concentration of 0.98 mol / L is obtained. Under the conditions of stirring and heating at 68 °C, the organic ligand solution is dropped into the precursor solution at a rate of 2.2 mL / min. The molar ratio of 2-methylimidazole to cobalt ions is 5.8:1. After all the organic ligand solution is dropped, continue to stir the obtained mixed solution at 68 °C for 4.2 h to obtain a reaction solution;

[0089] (2) Mix and stir the reaction solution and polyvinyl alcohol for 3.5 h. The addition amount of polyvinyl alcohol is 8.5 wt% of the mass of the reaction solution. Inject the mixed solution into a mold for directional freezing. First, cool down to -18 °C at a cooling rate of -1.8 °C / min and keep it warm for 0.8 h, then continue to cool down to -38 °C at a cooling rate of -0.8 °C / min and keep it warm for 3.2 h to obtain an aerogel matrix;

[0090] (3) Add silane coupling agent KH550 into an ethanol aqueous solution (the volume ratio of absolute ethanol to deionized water in the ethanol aqueous solution is 9:1). After mixing evenly, a silane coupling agent solution with a mass fraction of 2.1 wt% is obtained; Immerse the aerogel matrix in the silane coupling agent solution, oscillate at 42 °C for 15 h, then take out the aerogel matrix, wash it with ethanol, and place it in a vacuum dryer at 52 °C for 10.5 h to obtain the aerogel-based porous composite material.

[0091] Example 5

[0092] This example provides a preparation method of an aerogel-based porous composite material for sewage treatment, as Figure 1 shown, the preparation method specifically includes the following steps:

[0093] (1) Disperse cobalt nitrate in deionized water. After mixing evenly, a cobalt source solution with a concentration of 0.25 mol / L is obtained. Mix a nanocellulose solution with a mass fraction of 2 wt% and the cobalt source solution in a volume ratio of 2:1 to obtain a precursor solution. Disperse 2-methylimidazole in methanol. After mixing evenly, an organic ligand solution with a concentration of 1 mol / L is obtained. Under stirring and heating conditions at 70 °C, the organic ligand solution is dropped into the precursor solution at a rate of 2.5 mL / min. The molar ratio of 2-methylimidazole to cobalt ions is 6:1. After all the organic ligand solution is dropped, continue to stir the obtained mixture at 70 °C for 4 h to obtain a reaction solution.

[0094] (2) Mix the reaction solution and polyvinyl alcohol and stir for 4 h. The addition amount of polyvinyl alcohol is 9 wt% of the mass of the reaction solution. Inject the mixed solution into a mold for directional freezing. First, cool down at a rate of -2 °C / min to -20 °C and keep warm for 0.5 h. Then continue to cool down at a rate of -1 °C / min to -40 °C and keep warm for 3 h to obtain an aerogel matrix.

[0095] (3) Add silane coupling agent KH550 to an ethanol aqueous solution (the volume ratio of absolute ethanol to deionized water in the ethanol aqueous solution is 9:1). After mixing evenly, a silane coupling agent solution with a mass fraction of 2.2 wt% is obtained. Immerse the aerogel matrix in the silane coupling agent solution and oscillate at 45 °C for 12 h. Then take out the aerogel matrix, wash it with ethanol, and place it in a vacuum dryer at 55 °C for 10 h to obtain the aerogel-based porous composite material.

[0096] Example 6

[0097] This example provides a preparation method of an aerogel-based porous composite material for sewage treatment. The difference from Example 1 is that in step (1), the volume ratio of the nanocellulose solution to the cobalt source solution is adjusted to 1:1, and other operation steps and process parameters are exactly the same as those in Example 1.

[0098] Example 7

[0099] This example provides a preparation method of an aerogel-based porous composite material for sewage treatment. The difference from Example 1 is that in step (1), the volume ratio of the nanocellulose solution to the cobalt source solution is adjusted to 4:1, and other operation steps and process parameters are exactly the same as those in Example 1.

[0100] Example 8

[0101] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (1), the molar ratio of 2-methylimidazole in the organic ligand solution to cobalt ions in the cobalt source solution is adjusted to 4:1, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0102] Embodiment 9

[0103] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (1), the molar ratio of 2-methylimidazole in the organic ligand solution to cobalt ions in the cobalt source solution is adjusted to 7:1, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0104] Embodiment 10

[0105] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (2), the addition amount of polyvinyl alcohol is 6 wt% of the mass of the reaction solution, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0106] Embodiment 11

[0107] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (2), the addition amount of polyvinyl alcohol is 10 wt% of the mass of the reaction solution, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0108] Embodiment 12

[0109] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (2), the second freezing temperature is adjusted to -25 °C, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0110] Embodiment 13

[0111] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (2), the second freezing temperature is adjusted to -45 °C, and other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0112] Embodiment 14

[0113] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (3), the mass fraction of the silane coupling agent KH550 in the silane coupling agent solution is adjusted to 1.5 wt%, and the other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0114] Embodiment 15

[0115] This embodiment provides a method for preparing an aerogel-based porous composite material for sewage treatment. The difference from Embodiment 1 is that in step (3), the mass fraction of the silane coupling agent KH550 in the silane coupling agent solution is adjusted to 2.5 wt%, and the other operation steps and process parameters are exactly the same as those in Embodiment 1.

[0116] The aerogel-based porous composite materials prepared in Embodiments 1-15 of the present invention are used to treat printing and dyeing wastewater and petrochemical wastewater, specifically including:

[0117] The aerogel-based porous composite materials prepared in Embodiments 1-15 of the present invention are put into the printing and dyeing wastewater. The COD value in the printing and dyeing wastewater is 824 mg / L, the NH3-N value is 18.3 mg / L, the suspended solid content is 255 mg / L, the chromaticity value is 580 times, and the dosage is 3 kg / m 3 , and the concentrations of various pollutants in the treated printing and dyeing wastewater are tested after 10 days. The concentrations of various pollutants in the treated printing and dyeing wastewater are shown in Table 1.

[0118] The aerogel-based porous composite materials prepared in Embodiments 1-15 of the present invention are put into the petrochemical wastewater. The COD value in the petrochemical wastewater is 2820 mg / L, the NH3-N value is 58.6 mg / L, the suspended solid content is 236 mg / L, the petroleum content is 125.3 mg / L, and the dosage is 8 kg / m 3 , and the concentrations of various pollutants in the treated petrochemical wastewater are tested after 10 days. The concentrations of various pollutants in the treated petrochemical wastewater are shown in Table 2.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123] It can be seen from the test data provided in Table 1 and Table 2 that the effluent water quality of Examples 1-5 is comprehensively better than the national standard requirements of printing and dyeing wastewater (GB 4287-2012 "Discharge Standard of Water Pollutants for the Textile Dyeing and Finishing Industry") and petrochemical wastewater (GB 31571-2015 "Discharge Standard of Pollutants for the Petrochemical Industry"). Through the combination of a multi-level pore structure and ZIF-67 photocatalysis, the present invention realizes efficient and stable sewage treatment performance, and is particularly suitable for the advanced treatment of high-difficulty printing and dyeing wastewater and petrochemical wastewater.

[0124] It can be seen from the test data of Example 1, Example 6 and Example 7 that the effluent water quality of Example 6 and Example 7 is inferior to that of Example 1. This is because the dosage of the nanocellulose solution in Example 6 is too small, resulting in the aggregation of ZIF-67 crystals, blocking the pores, and reducing the adsorption and catalytic efficiency. In Example 7, the dosage of the nanocellulose solution is too large, affecting the structural stability, resulting in pore collapse, and the interception efficiency of pollutants decreases.

[0125] It can be seen from the test data of Example 1, Example 8 and Example 9 that the effluent water quality of Example 8 and Example 9 is inferior to that of Example 1. This is because the dosage of 2-methylimidazole in Example 8 is too small, resulting in a decrease in the crystallinity of ZIF-67 and an incomplete mesoporous structure. At the same time, it will also affect the activity of Lewis acid centers and the photocatalytic effect of the material. In Example 9, the dosage of 2-methylimidazole is too large, and the organic ligand occupies the lattice sites, hindering Co 2+ from participating in the catalytic reaction and affecting the photocatalytic effect of the material.

[0126] It can be seen from the test data of Example 1, Example 10 and Example 11 that the effluent water quality of Example 10 and Example 11 is inferior to that of Example 1. This is because the dosage of polyvinyl alcohol in Example 10 is too small, resulting in a loose nanocellulose network and the loss of ZIF-67 during the freezing process, affecting the photocatalytic effect of the material. In Example 11, the dosage of polyvinyl alcohol is too large, and the hydrogen bond network is over-crosslinked, resulting in hindered ice crystal growth and a decrease in porosity, and the interception efficiency of pollutants decreases.

[0127] It can be seen from the test data of Example 1, Example 12 and Example 13 that the effluent water quality of Example 12 and Example 13 is inferior to that of Example 1. This is because the second freezing temperature in Example 12 is too low, resulting in rapid formation of ice crystal nuclei, rough pore walls, and uneven loading of ZIF-67. At the same time, the deterioration of the pore structure reduces the local concentration of catalytic sites and affects the photocatalytic effect of the material. In Example 13, the second freezing temperature is too high, resulting in slow ice crystal growth and chaotic orientation, broad pore size distribution, and a decrease in the interception efficiency of pollutants.

[0128] It can be seen from the test data of Example 1, Example 14 and Example 15 that the water quality of the effluent in Example 14 and Example 15 is inferior to that in Example 1. This is because the mass fraction of the silane coupling agent KH550 in Example 14 is too low, the coverage rate of the hydrophobic layer is insufficient, and the penetration of water molecules interferes with the catalytic reaction, affecting the photocatalytic effect of the material. In Example 15, the mass fraction of the silane coupling agent KH550 is too high, forming a dense hydrophobic layer, which hinders the diffusion of pollutants, increases the mass transfer resistance, and reduces the interception efficiency of pollutants.

[0129] The applicant declares that the above description is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by any person skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A preparation method of an aerogel-based porous composite material for sewage treatment, characterized in that, The preparation method includes: Mixing a nanocellulose solution with a cobalt source solution to obtain a precursor solution, and dropping an organic ligand solution into the precursor solution under stirring and heating conditions to obtain a reaction solution; mixing the reaction solution with polyvinyl alcohol uniformly and then injecting the mixture into a mold for directional freezing to obtain an aerogel matrix; performing hydrophobic modification on the aerogel matrix to obtain the aerogel-based porous composite material. The volume ratio of the nanocellulose solution to the cobalt source solution is (2 - 3):

1. The molar ratio of 2-methylimidazole in the organic ligand solution to cobalt ions in the cobalt source solution is (5 - 6):

1. The addition amount of polyvinyl alcohol is 7 - 9 wt% of the mass of the reaction solution.

2. The preparation method according to claim 1, characterized in that, The mass fraction of the nanocellulose solution is 1 - 2 wt%. The cobalt source solution is composed of cobalt nitrate and deionized water. The concentration of cobalt nitrate in the cobalt source solution is 0.15 - 0.25 mol / L.

3. The preparation method according to claim 1, characterized in that The organic ligand solution is composed of 2-methylimidazole and methanol. The concentration of 2-methylimidazole in the organic ligand solution is 0.9 - 1 mol / L. The dropping rate of the organic ligand solution is 1.5 - 2.5 mL / min. The heating temperature when the organic ligand solution is dropped into the precursor solution is 60 - 70 °C. After all of the organic ligand solution is dropped, continue to mix and stir the obtained mixture for 4 - 5 h to obtain the reaction solution.

4. The preparation method according to claim 1, wherein The mixing and stirring time of the reaction solution and the polyvinyl alcohol is 2 - 4 h.

5. The preparation method according to claim 1, wherein The directional freezing process includes: Cooling to a first freezing temperature at a first cooling rate and holding the temperature, and then continuing to cool to a second freezing temperature at a second cooling rate and holding the temperature.

6. The preparation method according to claim 5, wherein The first cooling rate is -1 to -2 °C / min. The first freezing temperature is -15 to -20 °C. The holding time at the first freezing temperature is 0.5 - 1.5 h. The second cooling rate is -0.5 to -1 °C / min. The second freezing temperature is -30 to -40 °C. The holding time at the second freezing temperature is 3 - 4 h.

7. The preparation method according to claim 1, characterized in that, The hydrophobic modification treatment includes: Soaking the aerogel matrix in a silane coupling agent solution, oscillating and heating, then taking out the aerogel matrix, washing it with ethanol and then performing vacuum drying to obtain the aerogel-based porous composite material.

8. The preparation method according to claim 7, wherein The silane coupling agent solution is composed of a silane coupling agent and an ethanol aqueous solution. The mass fraction of the silane coupling agent in the silane coupling agent solution is 1.8 - 2.2 wt%. The heating temperature when the aerogel matrix is soaked in the silane coupling agent solution is 35 - 45 °C. The soaking time of the aerogel matrix in the silane coupling agent solution is 12 - 24 h. The temperature of the vacuum drying is 45 - 55 °C. The time of the vacuum drying is 10 - 12 h.

9. An aerogel-based porous composite material for sewage treatment prepared by using the preparation method according to any one of claims 1 to 8.

10. Use of the aerogel-based porous composite material for sewage treatment according to claim 9, characterized in that, The aerogel-based porous composite material is used for sewage treatment.

Citation Information

Patent Citations

  • Preparation method of polyvinyl alcohol / bagasse nano-cellulose aerogel

    CN108752623A

  • Anisotropic nano-cellulose aerogel and preparation method and device thereof

    CN110172185A

  • Preparation method of cellulose nano-fibril aerogel suitable for layer-by-layer self-assembly process

    CN111621056A

  • Wave-absorbing material with oriented layered structure and preparation method of wave-absorbing material

    CN119209028A

  • Carbon-loaded MOF derivative aerogel and preparation method thereof

    CN119236812A

Cited By

  • Aerogel composite material as well as preparation method and application thereof

    CN121016710A

  • An aerogel composite material, its preparation method and application

    CN121016710B